Ascending of Cycloaddition Strategy for N–O Heterocycles - Ghosh, Prasanjit; Mondal, Swati Lekha; Baidya, Mahiuddin (Synthesis, 2022)
The N–O heterocycles are biologically relevant scaffolds and versatile building blocks in contemporary organic synthesis. In this short review, we showcase the involvement and elevation of various cycloaddition strategies towards the production of the N–O heterocycles; 1,2-oxazines and 1,2-oxazinanes, 1,2-oxazepanes, and 1,2-oxazetidines. An overview of the advantages and challenges associated with these synthetic endeavors is provided.1 Introduction2 Six-Membered N–O Heterocycles (1,2-Oxazines and 1,2-Oxazinanes)3 Seven-Membered N–O Heterocycles (1,2-Oxazepanes)4 Four-Membered N–O Heterocycles (1,2-Oxazetidines)5 Summary and Outlook
Keywords: cycloaddition; nitroso Diels–Alder reaction; nitrones; oxazines; oxazetidines; oxazepane; cyclopropanes; cascade reaction